2023
DOI: 10.46815/jk.v12i1.133
|View full text |Cite
|
Sign up to set email alerts
|

Efikasi Diri Siswa Sekolah sebagai Layperson Pemberian Pertolongan Pertama Cedera

Abstract: Cedera dapat dialami siapa saja tanpa melihat usia dan usia anak sekolah menjadi salah satu kelompok rentan cedera. Lingkungan sekolah menjadi lokasi tertinggi kedua tempat terjadinya cedera. Tindakan pemberian pertolongan pertama pada kasus cedera di lingkungan sekolah menjadi hal penting agar siswa dapat menjadi seorang layperson yang ideal diperlukan dasar keyakinan diri. Tujuan penelitian ini adalah mengidentifikasi efikasi diri anak sekolah menengah pertama sebagai Layperson dalam penanganan kasus cedera.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The school environment is the second highest location where injuries occur due to the unsafe condition of the school environment and the lack of understanding of students in the school environment regarding the concept of danger and first aid measures when injuries occur (Susanti, & Sari, 2017) Based on the results of previous studies, the self-efficacy of school students as laypersons in first aid for injuries is an important aspect to consider. Several studies have shown that the self-efficacy and knowledge level of school children about first aid is still low (Nastiti et al, 2023), This may be due to their age and lack of previous experience in dealing with injuries (Granello et al, 2022). Efforts are needed to increase the confidence and knowledge of school-aged lay people, which can be initiated by health workers (Mathew et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The school environment is the second highest location where injuries occur due to the unsafe condition of the school environment and the lack of understanding of students in the school environment regarding the concept of danger and first aid measures when injuries occur (Susanti, & Sari, 2017) Based on the results of previous studies, the self-efficacy of school students as laypersons in first aid for injuries is an important aspect to consider. Several studies have shown that the self-efficacy and knowledge level of school children about first aid is still low (Nastiti et al, 2023), This may be due to their age and lack of previous experience in dealing with injuries (Granello et al, 2022). Efforts are needed to increase the confidence and knowledge of school-aged lay people, which can be initiated by health workers (Mathew et al, 2016).…”
Section: Introductionmentioning
confidence: 99%